Association between lactate to hematocrit ratio and 30-day all-cause mortality in patients with sepsis: a retrospective analysis of the Medical Information Mart for Intensive Care IV database - Duan, Wentao; Yang, Feng; Ling, Hua; Li, Qiong; Dai, Xingui (Frontiers in Medicine, 2024)
The role of the lactate to hematocrit ratio (LHR) in predicting all-cause mortality among sepsis patients has yet to be evaluated. Therefore, this study aims to explore the relationship between LHR and 30-day all-cause mortality in sepsis patients.This study is a retrospective analysis; the data was sourced from the Medical Information Mart for Intensive Care IV (MIMIC-IV, version 2.0). We included adult sepsis patients who were admitted to the ICU for the first time as our study subjects. We evaluated the predictive ability of admission LHR for 30-day all-cause mortality using a multivariate Cox regression model, receiver operating characteristic (ROC) curve analysis, Kaplan-Meier curves, and subgroup analyses.Results: A total of 3829 sepsis patients participated in this study. Based on survival within 30 days of admission, patients were divided into a survival group (3504 patients) and a non-survival group (325 patients), with a mortality rate of 8.5%. The multivariate Cox regression analysis showed that LHR is an independent predictor of 30-day allcause mortality in sepsis patients after admission (hazard ratio 1.18; 95% CI, 1.08-1.29; P<0.001). The area under the curve (AUC) for LHR was 74.50% (95% CI: 71.6%-77.50%), higher than arterial blood lactate (AUC=71.30%), hematocrit (AUC=64.80%), and shows no significant disadvantage compared to qSOFA, SOFA, and SAPS II. We further evaluated combining LHR with qSOFA score to predict mortality in sepsis patients, which shows more clinical significance. The optimal cutoff value determined by the ROC curve for distinguishing between the survival and non-survival groups was 6.538. Kaplan-Meier curve method showed that patients with LHR≥6.538 had significantly higher all-cause mortality within 30 days of admission compared to those with LHR<6.538 (P<0.001). Subgroup analysis showed significant interactions between LHR and age group, sex group, and the group with concomitant acute respiratory failure (interaction P=0.001-0.005).LHR is an independent predictor of all-cause mortality in sepsis patients after admission, with superior predictive ability compared to blood lactate or hematocrit alone.